The combined treatment of vitamin A eye drops, oral vitamin A , and oral doxycycline in meibomian gland dysfunction. - Suhardjo, Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: The frequency of meibomian gland dysfunction (MGD) patients is increasing in elderly and especially in female. Meanwhile the relationship of dry eye with meibomian gland dysfunction is close. Dry condition of eye will result in epitheliopathy, susceptibility to superinfection, scarring sequelae, and neovascularization in ocular surface. Vitamin A can prevent epitheliopathy and disturbance of tear film stability. Oral doxycycline inhibits lipase activity of any attendant microorganism.Objective: To evaluate the effect of systemic combined therapy vitamin A and doxycycline with vitamin A eye drops versus vitamin A eye drop and oral doxycycline in the management of meibomian gland dysfunction.Methods: The design of study was double blind randomized clinical trial. Setting was at Dr Sardjito Eye Clinics. The subjects were 60 MGD patients aged 50-79 years old, male and female were enrolled in this study and divided into two groups. The group I received vitamin A eye drops and oral doxycycline of 100 mg for 4 weeks. The group II was treated with oral vitamin Aof 6000 IU two times per day for 3 weeks, vitamin A eye drops, and oral doxycycline of 100 mg for 12th weeks. Both groups were followed at 4, 8, and 12 weeks for clinical signs, tear production (Schirmer test), quality of mucine (ferning test), and quality of ocular surface (rose bengal test).Results: Improvement was obtained in both group, in clinical signs of MGD as well as in tear production, quality of mucine, and ocular surface condition. There was no significant difference between both groups (p=0.58, RR =0.86, 95%, CI 0.21-3.50). The combined treatment of oral vitamin A, vitamin A eye drops and oral doxycycline of 100 mg in 12 weeks results in similar improvement with treatment by vitamin A eye drops and oral doxycycline in 4 weeks in MGD patients. The side effect of doxycycline was gastrointestinal problem in 2 patients.Conclusion: The result of this study supports that four weeks treatment is sufficient in achieving improvement of meibomian gland dysfunction patients.Key words: Vitamin A - doxycycline - meibomian gland dysfunction - four weeks